Managing Mental Health: Psychological Stress and Coping Mechanisms Among Medical Students - Jitendra Rawat (International Journal of Medical Science and Public Health Research, 2025)
Medical students are often subjected to high levels of psychological stress due to the demanding nature of their training, which includes rigorous coursework, clinical practice, and emotional challenges. This study aims to explore the psychological stress experienced by medical students and examine the coping strategies they employ to manage stress. A comprehensive survey was conducted with medical students from various years, assessing their stress levels, sources of stress, and the coping mechanisms they use to manage these challenges. The study identifies key stressors, including academic pressure, long working hours, and the emotional toll of patient care, and explores a range of coping strategies such as problem-solving, emotional regulation, social support, and avoidance. The findings suggest that while many students utilize adaptive coping strategies, a significant number rely on maladaptive methods, such as avoidance or substance use, which can negatively impact their mental health and academic performance. Based on the results, the study recommends targeted mental health interventions and support systems to help medical students develop healthier coping mechanisms, improve resilience, and reduce the risk of burnout.